Uji Aktivitaas Antimikroba Ekstrak Etanol Daun Kelor (Moringa oleifera L.) Terhadap Bakteri Staphylococcus aureus, Escherichia coli, dan Jamur Candida albicans - Putri, Anggy utama; Harisandy, Alvian (JURNAL KESEHATAN TERAPAN, 2024)
The increasing resistance of microorganisms to antibiotics has become a global problem in the field of health. The main causes of antibiotic resistance include inappropriate use of antibiotics, the use of plants as drugs is an alternative method to reduce the level of resistance to antibiotics. One of the plants that can be used as medicine is the Moringa plant. Moringa plants can be used as antioxidants, antibacterial, antifungal, and anti-inflammatory. This study was conducted to test the antimicrobial activity of ethanol extract of Moringa leaves (Moringa oleifera L.) against Staphylococcus aureus, Escherichia coli and Candida albicans fungi. This study aims to determine the antimicrobial effect of Moringa leaves (Moringa oelifera L.) against several microbes. The antimicrobial activity test of moringa leaf ethanol extract was carried out using the agar diffusion method, with concentrations of 10%, 20% and 30%. The results showed the average inhibition zone diameter of Escherichia coli bacteria was 9.5 mm, 10.23 mm and 12.36 mm, Staphylococcus aureus was 7.86 mm, 9.53 mm and 10.33 mm, and Candida albicans fungus was 6.43 mm, 7.8 mm, and 8.26 mm. The results of the study of ethanol extract at a concentration of 30% showed the greatest antimicrobial activity on Escherichia coli bacteria with an inhibition zone of 12.36 mm including the strong category.